THE EFFECTIVENESS OF MARKETING INFORMATION IN SUPPORTING AND RATIONALIZING MARKETING MIX DECISIONS: A CASE STUDY OF A SAMPLE OF IRAQI ECONOMIC COMPANIES (World Economics and Finance Bulletin, 2024)
Marketing is considered an effective tool in clarifying the nature of the product and its features, how to use it to target groups, and promoting the product or service, which contributes to rationalizing decisions related to the marketing mix in economic companies. Therefore, the research aims to shed light on the impact of the effectiveness of marketing information in supporting and rationalizing decisions related to the marketing mix for Iraqi economic companies. In order to solve the research problem and in pursuit of achieving its objectives, the research relies on the descriptive analytical approach. The study reached many results, perhaps the most prominent of which is the presence of a very high level of application of the marketing mix in Iraqi economic companies, where the arithmetic mean value reached 4.253 with a standard deviation of 0.687. The study also found that there is a strong, statistically significant direct correlation between the effectiveness of marketing information and supporting the decision-making process. It is evident that there is a statistically significant direct effect of the effectiveness of marketing information on supporting the decision-making process. It turns out that the more the level of effectiveness of marketing information increases by 1%, the greater the level of support for the decision-making process. Decision-making in Iraqi economic institutions by 0.636%,%, and therefore the study recommends increasing the level of awareness of company management on the necessity of providing all methods and means that contribute to increasing the administrative and marketing capacity of companies
Keywords: marketing; supporting decision rationalization; marketing mix